Self Care and Healing Amr Nahy's Perspective - Darin Rihhadatul ‘Aisy; Ernisah; Nadiyya Qurotul Aini; Neneng Maulayati; Safarudin (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
In the stressful modern life, the concepts of self-care and healing are very relevant. This research explores these concepts from an Islamic perspective through the Amr Nahy framework found in the Qur'an and Hadith. Islam views self-care and healing as part of a Muslim's spiritual and social responsibility, rather than an individualistic trend. Through a qualitative approach and literature review, this study discusses shar'i arguments and maqasid sharia principles to show that Islam supports a balanced life, and encourages quality productivity that is worthy of worship.